Вплив технічного обслуговування і ремонту на надійність машин та обладнання при використанні біологічних рідин - Журавель, Дмитро Павлович; Журавель, Дмитрий Павлович; Zhuravel, Dmytro (ТДАТУ, 2020)
UK: Робота присвячена обґрунтуванню впливу технічного обслуговування і ремонту на надійність машин при експлуатації на біологічних паливномастильних матеріалах. Результати моделювання свідчать, що при існуючих характеристиках надійності тракторів і співвідношення вартості ремонтів найбільш економічним способом підтримки машини в працездатному стані є поточні профілактичні ремонти з діагностуванням. На підставі проведених досліджень, встановлено, що зниження ресурсу елементів і систем мобільної сільськогосподарської техніки при роботі на біологічних паливно-мастильних матеріалах пояснюється активним впливом метанолу біодизельного пального і вільних жирних кислот біооливи на матеріали основних елементів дизельного двигуна, системи змащення, гідростатичних і механічних трансмісій, гідросистем. Це призводить до руйнування поверхонь і збільшення зносів деталей трибоспряжень. Падіння ресурсу відбувається також через низьку стійкість ущільнюючих елементів, виготовлених із синтетичних каучуків, які активно взаємодіють з вільними жирними кислотами біологічних рідин. Встановлено, що при переході на біологічні паливно-мастильні матеріали трудомісткість ремонтнообслуговуючих заходів збільшується на 4,5 %, за рахунок збільшення ТО-1 на три обслуговування і ТО-2 на одне обслуговування, при терміні напрацювання - 6000 мото-годин. RU: Работа посвящена обоснованию влияния технического обслуживания и ремонта на надежность машин при эксплуатации на биотопливо-смазочных материалах. Результаты моделирования показывают, что при существующих характеристиках надежности тракторов соотношение стоимости ремонтов наиболее экономичным способом поддержки машины в работоспособном состоянии является текущие профилактические ремонты с диагностированием. На основании проведенных исследований установлено, что снижение ресурса элементов и систем мобильной сельскохозяйственной техники при работе на биологических горюче-смазочных материалах объясняется активным влиянием метанола биодизельного горючего и свободных жирных кислот биомасла на материалы основных элементов дизельного двигателя, системы смазки, гидростатических и механических трансмиссий, гидросистем. Это приводит к разрушению поверхностей и увеличению износов деталей трибосопряжений. Падение ресурса происходит также из-за низкой устойчивости уплотнительных элементов, изготовленных из синтетических каучуков, которые активно взаимодействуют со свободными жирными кислотами биологических жидкостей. При переходе на биологические ГСМ трудоемкость ремонтно-обслуживающих мероприятий увеличивается на 4,5 %, за счет увеличения ТО-1 на три и ТО-2 – на одно, в расчете на 6000 мото-часов наработки. EN: The work is devoted to the justification of the impact of maintenance and repair on the reliability of machines when operating on biofuel-lubricants. The simulation results show that with the existing tractor reliability characteristics and the ratio of the cost of repairs, the most cost-effective way of keeping the machine in working order is ongoing preventive repairs with diagnosis. The so-called "capital repairs" of tractors carried out at repair shops, due to the high cost, are not economically justified. Compared to preventive maintenance, they lead to an increase in total costs with damage from downtime by 24–40%, with an increase in the number of failures by 7– 13% and a duration of downtime by 13–42%. In this work, under the repair strategy should be the recovery of the machine through maintenance operations, replacement or simple repair (without the use of sophisticated equipment) of one or more parts. Current repair is considered, which involves the simultaneous elimination of several failures and / or the execution of works aimed at their prevention. In the latter case, such a repair is called current preventive. Based on the studies, it was found that the reduction in the life of elements and systems of mobile agricultural equipment when working on biological fuels and lubricants is explained by the active influence of methanol of biodiesel fuel and bio-free fatty acids on materials of the main elements of a diesel engine, lubrication system, hydrostatic and mechanical transmissions, hydraulic systems. This leads to the destruction of surfaces and an increase in wear of the parts of the friction units. The fall of the resource is also due to the low stability of sealing elements made of synthetic rubbers, which actively interact with free fatty acids of biological fluids. When switching to biological fuels, the complexity of repair and service measures increases by 4,5% due to the increase of TO-1 for three and TO-2 for one in the calculation of 6000 operating hours.
Влияние технического обслуживания и ремонта на надежность машин и оборудования при использовании биологических жидкостей
Influence of maintenance and repair on the reliability of machines and equipment when using biological liquids
Keywords: технічне обслуговування; ресурс; надійність; біологічні паливно-мастильні матеріали; ймовірність безвідмовної роботи; знос; працездатний стан; техническое обслуживание; надежность; биологические топливо-смазочные материалы; вероятность безотказной работы; износ; работоспособное состояние; maintenance; resource; reliability; biological fuel and lubricants; probability of trouble-free operation; wear and tear; working condition